2015
DOI: 10.1038/srep14784
|View full text |Cite
|
Sign up to set email alerts
|

Multicopper oxidase-1 is required for iron homeostasis in Malpighian tubules of Helicoverpa armigera

Abstract: Multicopper oxidases (MCOs) are enzymes that contain 10 conserved histidine residues and 1 cysteine residue. MCO1 has been extensively investigated in the midgut because this MCO is implicated in ascorbate oxidation, iron homeostasis and immune responses. However, information regarding the action of MCO1 in Malpighian tubules is limited. In this study, Helicoverpa armigera was used as a model to investigate the function of MCO1 in Malpighian tubules. Sequence analysis results revealed that HaMCO1 exhibits typi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…dMCO1's role in iron homeostasis was confirmed by RNAi knockdown experiments yielding increased longevity when flies fed on high iron food and a decreased iron accumulation in the body. The MCO gene family is conserved in coleopterans, lepidopterans and dipterans (Lang et al, 2012 ; Liu et al, 2015 ; Peng et al, 2015 ; Ye et al, 2015 ). An.…”
Section: Iron Transport Across Cell Membranesmentioning
confidence: 99%
“…dMCO1's role in iron homeostasis was confirmed by RNAi knockdown experiments yielding increased longevity when flies fed on high iron food and a decreased iron accumulation in the body. The MCO gene family is conserved in coleopterans, lepidopterans and dipterans (Lang et al, 2012 ; Liu et al, 2015 ; Peng et al, 2015 ; Ye et al, 2015 ). An.…”
Section: Iron Transport Across Cell Membranesmentioning
confidence: 99%
“…Two main Laccase genes, Laccase1 ( Lac1 / MCO1 ), and Laccase2 ( Lac2 / MCO2 ), have been described in insects. Lac1 is expressed in tissues such as salivary glands, midgut and Malpighian tubules and has been implicated in lignocellulose digestion, detoxification of secondary plant compounds, ascorbate and iron homeostasis, and immune defense in insects ( Gorman et al, 2008 ; Coy et al, 2010 ; Lang et al, 2012 ; Liu et al, 2015 ; Peng et al, 2015 ; Yang C.-H. et al, 2017 ; Wang et al, 2018 ; Zhang et al, 2018 ), while Lac2 is expressed primarily in the epidermis and has been associated with insect cuticular pigmentation and hardening as well as melanization immune response ( Arakane et al, 2005 ; Elias-Neto et al, 2010 ; Futahashi et al, 2011 ; Ye et al, 2015 ; Du et al, 2017 ; Nishide et al, 2020 ). Further, Lac2 has been related to mechanisms of insecticide cuticular resistance.…”
Section: Introductionmentioning
confidence: 99%
“…Two types of MCOs have been identified in various insect species. MCO1s are expressed generally in a number of organs in Manduca sexta , Drosophila melanogaster , Nephottetix cincticeps , Helicoverpa armigera , Nilaparvata lugens , and Triboleum castaneum (Dittmer et al, ; Hattori et al, ; Lang, Braun, Kanost, & Gorman, ; Liu et al, ; Peng et al, ; Ye, Pan, Kang, Lu, & Zhang, ), with associated ascorbate oxidase activities identified in several of these species (Peng et al, ). Meanwhile, MCO2s are laccases that are highly expressed in integument.…”
Section: Introductionmentioning
confidence: 99%